Bare minimum dinners ebook Recipes and strategies for doing less in the kitchen. - Helwig, Jenna (2024)
Easy recipes and shortcuts to spend less time in the kitchen—with fewer ingredients, less cleanup, Instant Pot and slow cooker options, meals made in 30 minutes or less, and other smart strategies Getting a home-cooked meal on the table every day is an admirable goal, but it shouldn't get in the way of your life! In Bare Minimum Dinners , Jenna Helwig—food director at Real Simple magazine—shares delicious, easy recipes so you can spend less time in the kitchen and more time enjoying your meal…or doing whatever else you want! Chapters include: Bare Minimum Time (30 minutes or less); Bare Minimum Ingredients (7 ingredients or less, including salt and olive oil); Bare Minimum Hands-On Time (slow-cooker and Instant Pot meals); Bare Minimum Clean-Up (one-pot/sheet pan/skillet meals); and Bare Minimum Sides (super-simple vegetables, salads, and grains so you can feel good about serving healthy, well-rounded dinners). Throughout, Jenna offers helpful tips—for example, how to keep salad greens fresh and at the ready, easy substitutions, and suggested supermarket brands—as well as easy ideas for dressing up or rounding out your meal.